Penyuluhan Bahaya Seks Bebas terhadap Kalangan Remaja di SMK Gelora Jaya Nusantara Medan Sumatera Utara - Nurdiana Tanjung; Yughni Aulia Nabila (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Wrong relationships influence sexual behavior, especially among teenagers. Casual sex is a relationship between a man and a woman that does not involve marriage. To prevent this from happening, the role of parents is very important. However, in reality, many parents feel that their children do not receive enough attention due to busy schedules and limited supervision time, so that many teenagers have problems. Apart from that, environmental influences (peers) can have a negative impact. The aim of this socialization activity is to spread knowledge through education about free sex among teenagers, and it is hoped that students' knowledge and behavior regarding free sex among teenagers will change. In Indonesia, sexual and reproductive health education for adolescents has not been fully accepted by society. This is influenced by the complex environment of social, cultural and religious life. Many people consider sexual and reproductive health education to be a taboo topic for the younger generation. This situation makes teenagers feel anxious when making reproductive health decisions. However, as time goes by, the influence of Western culture brings freedom and open access to information, thus providing opportunities for teenagers to take negative actions towards reproductive health.